Real-time TaqMan polymerase chain reaction to quantify the effects of different sources of dietary starch on Bifidobacterium in the intestinal tract of piglets - Zhentian Xiang, Hongwei Qi; Guoquan Han, Jingbo Liu; Zhiqing Huang, Bing Yu; Daiwen Chen (African Journal of Pig Farming, 2015)
Twenty-eight PIC male piglets (similar birth and parity, weaned at 21±1.5 days) were used to study the effect of the different sources of dietary starch on the number of Bifidobacteria in the digesta of the duodenum, jejunum, ileum, cecum and colon. Pigs were randomly assigned to one of four diets formulated with corn starch, wheat starch, tapioca or pea starch. The determined ratio of amylose to amylopectin for these starches was 0.21, 0.24, 0.12 and 0.52, respectively based on the 16s rRNA sequences of maximum species of Bifidobacterium from GenBank to design the primers and probe. TaqMan polymerase chain reaction was developed to quantify the number of Bifidobacterium. We used this assay to detect genomic DNA of Bifidobacterium in the intestinal tract digesta of piglets, including duodenum, jejunum, ileum, cecum and colon. Our results indicated that, developed new real-time quantitative PCR assays can be allowed for rapid, convenient, reproducible and steady quantification of the Bifidobacterium in the intestinal content of piglets. Additionally, the present study revealed that high amylose/amylopectin ratio of starches significantly enhanced the numbers of Bifidobacterium in all segments of intestine.